A solution-processed yttrium-doped ZnO thin film transistors with sol-gel derived yttrium oxide gate dielectric layer. (29th August 2018) - Kumar, Manoj; Jeong, Hakyung; Lee, Dongjin
Abstract: Yttrium-doped ZnO (YZO) thin film transistors (TFTs) are fabricated on sol-gel derived yttrium oxide (Y2 O3 ) dielectric layers by solution process. The sol-gel derived Y2 O3 layer annealed at 300 °C showed a leakage current density of less than 10 −6 A cm −2 at 10 V. Increasing the annealing temperature led to a decrease in the leakage current density by more than two orders of magnitude. The Y2 O3 dielectrics annealed at 300 °C exhibited crystalline phase, smooth surface and a high dielectric constant. The YZO TFTs built on a sol-gel derived Y2 O3 layer showed charge carrier mobility of 6.19 to 27.10 cm 2 V −1 s −1 upon annealing of YZO at 350 to 500 °C. The chemical composition was determined by x-ray photoelectron spectroscopy to confirm the doping of Y in the ZnO at all annealing temperatures. The results reveal the potential of Y2 O3 dielectric for developing low-temperature and high-performance electronic devices.